Creating the eXtension Family Caregiving Community of Practice - Sellers, Debra M.; Crocker, Andrew B.; Nichols, Allison; Kirby, Sarah D.; Brintnall-Peterson, Mary (My University, 2009)
The Family Caregiving Community of Practice, part of eXtension, provides a national one-stop site for Extension's caregiving educational resources. The developmental process of this community's creation is discussed within the "expansive learning" framework. Negatively, community members found too much emphasis on process and a lack of criteria for academic credit. Positively, they experienced increased knowledge, improved networking, and innovation. Recommendations for others creating communities are to: 1) promote the benefits of networking; 2) seek out others with similar passions; 3) provide graduated opportunities for learning; 4) help members transition from an individual perspective; and 5) provide systems for academic recognition.
Keywords: eXtension; Collaboration; Community of practice; Family caregiving; Online learning